Is "Bow" for an Arrow or for Hair? A Classroom Demonstration on Gender Differences in Interpreting Ambiguous Information. (October 2016) - Fa-Kaji, Naomi; Nguyen, Linda; Hebl, Mikki; Skorinko, Jeanine
This article details a classroom demonstration of how gender differences in cognitive schemas can result in men and women differentially interpreting the same information. Students heard a series of six homonyms (e.g., bow and nail) spoken aloud and wrote down the first word with which they free-associated each homonym. When hearing the words (e.g., bow), men were more likely to respond with a male-gendered word (e.g., arrow), whereas women were more likely to respond with a female-gendered word (e.g., hair). The demonstration is easy to administer, takes approximately 10 min, results in strong differences, and improves students' understanding of gender differences in cognitive schemas.